2014
DOI: 10.1210/jc.2013-3369
|View full text |Cite
|
Sign up to set email alerts
|

The HIV Protease Inhibitor Nelfinavir Down-Regulates RET Signaling and Induces Apoptosis in Medullary Thyroid Cancer Cells

Abstract: NFV has a wide spectrum of activity against MTC cells, and its cytotoxicity can be augmented by inhibiting autophagy. Expression of NFV molecular targets in metastatic MTC suggests that NFV has a potential to become a thyroid cancer therapeutic agent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 41 publications
3
32
0
Order By: Relevance
“…We have reported previously that NFV inhibited the viability of medullary thyroid cancer cells, decreased the level of RET protein and blocked the activation of RET downstream targets (phosphorylated ERK, phosphorylated AKT and p70S6K/pS6) (Kushchayeva et al 2014b). These findings suggested that NFV could be effective against differentiated thyroid cancer cells with mutations in the PI3K/AKT pathway, as well as in tumors with activating mutations in MAPK-BRAF-ERK signaling.…”
Section: Introductionmentioning
confidence: 65%
“…We have reported previously that NFV inhibited the viability of medullary thyroid cancer cells, decreased the level of RET protein and blocked the activation of RET downstream targets (phosphorylated ERK, phosphorylated AKT and p70S6K/pS6) (Kushchayeva et al 2014b). These findings suggested that NFV could be effective against differentiated thyroid cancer cells with mutations in the PI3K/AKT pathway, as well as in tumors with activating mutations in MAPK-BRAF-ERK signaling.…”
Section: Introductionmentioning
confidence: 65%
“…MTC can present as a hereditary disease in 25% of cases as a phenotype of multiple endocrine neoplasia type II (MEN2) syndromes A and B, or as a sporadic disease in 75% of cases (10). Constitutively activating mutations in RET cause almost all hereditary occurrences and approximately 50% of sporadic cases (11); thus, this protein has been the primary focus of drug development.…”
Section: Introductionmentioning
confidence: 99%
“…The HIV-protease inhibitor nelfinavir has been shown to decrease RET expression and induce apoptosis in medullary thyroid cancer cells, but clinical studies are needed to prove its efficacy in treating MTC [62].…”
Section: Experimental Therapiesmentioning
confidence: 99%